Phenylbutyrate-induced glutamine depletion in humans: effect on leucine metabolism - Darmaun, Dominique; Welch, Susan; Rini, Annie; Sager, Brenda K; Altomare, Astride; Haymond, Morey W (American journal of physiology: endocrinology and metabolism, 1998)
The present study was designed to determine whether sodium phenylbutyrate (ΦB) acutely induces a decrease in plasma glutamine in healthy humans, and, if so, will decrease estimates of whole body protein synthesis. In a first group of three healthy subjects, graded doses (0, 0.18, and 0.36 g ⋅ kg ⋅ day ) of ΦB were administered for 24 h before study: postabsorptive plasma glutamine concentration declined in a dose-dependent manner, achieving an ≈25% decline for a dose of 0.36 g ΦB ⋅ kg ⋅ day . A second group of six healthy adults received 5-h infusions ofl-[1- C]leucine andl-[1- C]glutamine in the postabsorptive state on two separate days: 1) under baseline conditions and 2) after 24 h of oral treatment with ΦB (0.36 g ⋅ kg ⋅ day ) in a randomized order. The 24-h phenylbutyrate treatment was associated with 1) an ≈26% decline in plasma glutamine concentration from 514 ± 24 to 380 ± 15 μM (means ± SE; P < 0.01 with paired t-test) with no change in glutamine appearance rate or de novo synthesis; 2) no change in leucine appearance rate (R ), an index of protein breakdown (123 ± 7 vs. 117 ± 5 μmol ⋅ kg ⋅ h ; not significant); 3) an ≈22% rise in leucine oxidation (Ox) from 23 ± 2 to 28 ± 2 μmol ⋅ kg ⋅ h ( P < 0.01), resulting in an ≈11% decline in nonoxidative leucine disposal (NOLD = R - Ox), an index of protein synthesis, from 100 ± 6 to 89 ± 5 μmol ⋅ kg ⋅ h ( P < 0.05). The data suggest that, in healthy adults, 1) large doses of oral phenylbutyrate can be used as a "glutamine trap" to create a model of glutamine depletion; 2) a moderate decline in plasma glutamine does not enhance rates of endogenous glutamine production; and 3) a short-term depletion of plasma glutamine decreases estimates of whole body protein synthesis.